Konflik dan Damai Sebagai Isu-isu Misiologis Di Indonesia Dewasa Ini - Sudhiarsa, Raymundus I Made (Perspektif, 2006)
Ethnic and religious conflicts and violence have spread throughout the archipelago, not only in the last few years, but also since the independence of the Republic (1945). They look like a 'repetitive ritual' of the people and it seems that nobody nor any institution could stop them, neither the government. How- ever, there are always people of good will who try to minimize the tension of the conflicts and the victims of all these indiscriminate violence. This article tries to examine the problem from the mission and pastoral perspective of the Church, namely, from her fundamental and main call to build up peace throughout the country. Therefore, issues on ethnic-religious conflicts, violence and peace should be the core of the Church's mission agenda for the coming few decades.